Effects of a Theatrical Improvisation programme on students' motor creativity. Issue 2 (3rd April 2021) - Méndez Martínez, Emilio; Fernandez-Rio, Javier
ABSTRACT: The goal was to assess the effects of a Theatrical Improvisation programme on students' motor creativity. 163 Secondary Education students participated: the experimental group, who experienced a Theatrical Improvisation unit, and the comparison group, who experienced a Drama in Education unit (based on the current Spanish educational law). A pretest, posttest, quasi-experimental, comparison group design was followed. Results showed that the students who experienced Theatrical Improvisation increased significantly more the four dimensions of motor creativity (Fluency, Flexibility, Imagination, Originality) assessed. Creative programmes based on Theatrical Improvisation are interesting to progressively push towards the needed global educational change.